Green nickel/nickel oxide nanoparticles for prospective antibacterial and environmental remediation applications. Issue 6 (15th March 2022) - Ali, Tanveer; Warsi, Muhammad Farooq; Zulfiqar, Sonia; Sami, Abdul; Ullah, Sana; Rasheed, A.; Alsafari, Ibrahim A.; Agboola, Philips O.; Shakir, Imran; Baig, Mirza Mahmood
Abstract: The extensive use of broad-spectrum antibiotics has resulted in antibiotic resistance for many human pathogenic bacteria making multi-drug resistance an increasing issue in the management of various infectious diseases. The current research focused on the green synthesis of nickel/nickel oxide nanoparticles (Ni o /NiO nanoparticles) using seeds extract of Lactuca Serriola, bactericidal effect on human pathogenic bacteria and the photocatalytic activity. Highly crystalline nature of Ni o /NiO nanoparticles was confirmed by X-ray diffraction (XRD). Infrared spectra of seeds extract of Lactuca Serriola (LS) evidenced the presence of many functional groups of phytochemicals acting as reducing or capping agents. From field emission scanning electron microscopic (FESEM) images of Ni o /NiO nanoparticles, it was clearly observed that the particles were slightly spherical in shape with size <100 nm. The Ni o /NiO nanoparticles were also tested against eight pathogenic bacteria ( Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis, Basilus subtilis, Basilus pumilus, Micrococcus luteus, E. coli and Bordetella bronchiseptica ) which displayed significant antibacterial activity at low doses and almost complete inhibition at optimized concentration. From the bandgap study, the reduced bandgap energy value of 1.57 eV indicated its potential semiconductor photocatalytic behavior. Higher degradation efficiency against the model contaminant crystal violet dye, possibility of multiple degradation mechanisms and simple recovery suggested that the green synthesized Ni o /NiO nanoparticles might be best suitable candidates for environmental remediation applications.